Effect of dietary sodium restriction on body water, blood pressure, and inflammation in hemodialysis patients: a prospective randomized controlled study - Rodrigues Telini, Lidiane Silva [UNESP]; de Carvalho Beduschi, Gabriela [UNESP]; Caramori, Jacqueline Socorro Costa Teixeira [UNESP]; Castro, João Henrique [UNESP]; Martin, Luis Cuadrado [UNESP]; Barretti, Pasqual [UNESP] (Springer Nature, 2013)
Purpose: Accumulating evidence suggests an association between body volume overload and inflammation in chronic kidney diseases. The purpose of this study was to evaluate the effect of dietary sodium reduction in body fluid volume, blood pressure (BP), and inflammatory state in hemodialysis (HD) patients. Methods: In this prospective controlled study, adult patients on HD for at least 90 days and those with C-reactive protein (CRP) levels ≥0.7 mg/dl were randomly allocated into two groups: group A, which included 21 patients treated with 2 g of sodium restriction on their habitual diet; and group B, which included 18 controls. Clinical, inflammatory, biochemical, hematological, and nutritional markers were assessed at baseline and after 8 and 16 weeks. Results: Baseline characteristics were not significantly different between the groups. Group A showed a significant reduction in serum concentrations of CRP, tumor necrosis factor-α, and interleukin-6 during the study period, while BP and extracellular water (ECW) did not change. In group B, there were no changes in serum concentrations of inflammatory markers, BP, and ECW. Conclusions: Dietary sodium restriction is associated with the attenuation of the inflammatory state, without changes in BP and ECW, suggesting inhibition of a salt-induced inflammatory response. © 2013 Springer Science+Business Media Dordrecht.
Keywords: Blood pressure; Dietary sodium restriction; Hemodialysis; Inflammation; Sodium; Volume